Polypharmacy, an option prior to clozapine?: a case report - Amer Siddiq AN, (Penerbit UKM, 2008)
This is a report of a patient on multiple antipsychotic medications for the treatment of schizophrenia. Often, polypharmacy is not encouraged, however, with the advent of newer atypical antipsychotic agents, this practice may need review. This case will be used to highlight the rare instances when polypharmacy may be useful prior to the commencement of clozapine for the treatment of schizophrenia